Stabilization of Pristine Low Resistive State in a Ruthenium(II)‐Polymer of a Hexadentate Schiff Base Ligand: Synthesis, Characterization, and Application as Non‐Volatile Memory Device. Issue 32 (21st July 2020) - Oberoi, Deepa; Dagar, Parveen; Shankar, Uday; Sahu, Satyajit; Bandyopadhyay, Anasuya
Abstract : Metallo‐supramolecular polymers offer ample opportunity to develop new emergent materials with the potential for applications as future memories. In this context, we have synthesized a novel hybrid polymer of our developed Schiff base ligand with Ru(II)‐metal ion. The main objective of this study is to understand the effect of changing central metal ion on the ligand field stabilization energy, and the band gap of material as the biting angle of organic moiety changes accordingly with a change in cationic radius of the central metal ion. Furthermore, we have also investigated the application in non‐volatile memory devices. Complete characterization of the newly synthesized hybrid polymer has been performed to establish its structure as well as oxidation state of the central metal ion. A comparative study of the present case and the previously reported Fe(II)‐polymer provides a clear insight into the effect of incorporating a bigger size metal ion in the polymer chain. Non‐volatile memory properties of the polymer have shown a rare behaviour of Negative Differential Resistance (NDR) along with the Low Resistive State (LRS) as its pristine state. Remarkable charge retention and endurance test have also been demonstrated. Abstract : In search of novel, non‐volatile memory materials from Schiff base ligands, we have synthesized a low‐cost hybrid polymer with Ru‐metal ion. This diamagnetic neutral complex shows dissimilar behaviour to that of its Fe analog. The butterfly I–V curve from this redox non‐innocent Ru‐poly shows an uncommon low resistive state as its pristine state with long charge retention and good repeatability.